Status of Mechanised Trawl Fishing Fleet of Cochin, Kerala - Inwati, Lalima; M P, Remesan; P H, Dhiju das; B, Manoj kumar; Sebastian, Mathew; Amrutha R. Krishnan; Edwin, Leela (Fishery Technology, 2022)
Trawl fishing is an important element of maritime fishing in the state of Kerala, southwest coast of India. With the increasing pressure of fishing in coastal waters, fishermen working in the mechanized trawl fishing sector have been forced to venture into deeper waters for identification of new fishing grounds and better catch. There have been significant changes in trawl fishery since its introduction and changes in the number and capacity of fishing vessels have increased several times over the past three decades. In this paper, an attempt has been made to document major shift in length overall (LOA), installed engine horsepower of the trawlers, head rope length and wing mesh size from 1955 to 2021. This study reveals that trawlers with LOA of 41.4 m, and engine up to 591 hp were recently introduced into the fleet. Similarly, the head rope length of all trawl nets was in the range 45.0 -160 m. A glaring trend in increasing the wing mesh size of fish trawls and cephalopod trawls were also observed from Kerala. The statutory requirement of square mesh codend were not found to be in use. This study shows an alarming situation in the trawl fishery of Kerala and there is an urgent need for strict implementation of regulations with regard to vessel size, engine power, size of the trawl, codend type and mesh size. Periodic inspection of fishing gear and catch to ensure MLS is highly essential to protect the fishery resources.